Alternativa metodológica para definição da vazão ecológica em trechos de vazão reduzida em hidrelétricas - Buenaga, Fernanda Vianna Amaral de Souza Cruz (2019)
The concern about environmental issues has become increasingly present and conflicting in the planning process of all sectors of society. The electric sector was a pioneer in the consideration of environmental criteria, based on the development of instruments to evaluate environmental impacts, including the reduction of flow Currently there are several methodologies for the evaluation of the ecological flow of rivers, and most of these methods consider only hydrological and / or hydraulic data, making it complex to define a flow that allows the maintenance of the aquatic biota. Even holistic approaches privilege one aspect to the detriment of others, including energy losses. In order to integrate the hydrological, hydraulic and ecological aspects, a methodological alternative was proposed, through multiple linear regression, for the definition of the Ecological Flow. Multiple regression was used in order to improve the model developed to explain the behavior of the independent variables It was verified that the construction of the model for the determination of the flow met all the necessary premises for the Multiple Linear Regression, being considered valid for all the analyzed seasonalities. Finally, the test of the determined equations showed that the methodological alternative presented more specific results for the determination of the flow, presenting physico-chemical and biotic variables. In addition to considering the seasonality of the water bodies, ensuring the hydrological pulses necessary for the maintenance of life. In addition, dual dynamic stochastic programming was used using the SDDP model to evaluate the energy loss.